Micromagnetics and Recording Materials - Wei, Dan.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
"Micromagnetics and Recording Materials" is a book trying to give a systematic theory of computational applied magnetism, based on Maxwell equations of fields and Landau-Lifshitz equations of magnetic moments. The focused magnetic materials are magnetic recording materials utilized in computer hard disk drives. Traditionally, (3z(BMicromagnetics(3y (Bincludes the areas of "magnetization curve theory", (3z(Bdomain theory" and (3z(Bread and write process analyses in recording systems(3y(B. As Springer Briefs, this book includes the first two areas of micromagnetics. M-H loops of hard magnetic thin film media, soft magnetic layers and Tunneling MagnetoResistive spin valves are solved based on the microstructures of thin films. Static domain structures and dynamic switching processes are analyzed in the arbitrary-shaped magnetic devices such as write head pole tips and magnetic force microscope tips. The book is intended for researchers who are interested in applied magnetism and magnetic recording in all disciples of physical science.s
Exordium -- Maxwell Equations and Landau-Lifshitz Equations -- Microstructure and Hysteresis Loop -- Domain Structure and Dynamic Process.
Keywords: Magnetism; Computer engineering; Optical materials; Materials Science; Optical and Electronic Materials; Magnetism, Magnetic Materials; Electrical Engineering